Cloud and Gas Ionisation in Atmosphere of Gas-Giant Planets. Issue Volume 8:Issue S293(2012) (29th April 2014) - Helling, Ch.; Jardine, M.; Stark, C.; Rimmer, P.; Diver, D.
Abstract: The steady increase of the sample of know extrasolar planets broadens our knowledge and at the same time, reveals our lack of understanding. Habitability is a wide expression, needing planet formation theory and microphysics of cloud formation at the same time. The habitability of a planet depends, amongst other things, on how much radiation reached the ground and how much of potentially dangerous radiation is absorbed on the way through the atmosphere. For this, we need to understand cloud formation and it's impact on the atmosphere. We have studied the formation of mineral clouds on planetary atmospheres by a kinetic approach which allows us to predict the size distribution and material composition of the cloud particles. With these results we show that mineral cloud particles can be electrically charged and at which point inside a cloud charge separation will cause an electric field breakdown. Such streamer processes result in an extreme increase of the local number of free charges. Given the strong magnetic field in Brown Dwarfs and maybe in giant gas planets, these charges will than be accelerated upward out of the atmosphere where they become detectable as radio emission.